Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/0194599818777195
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Nasal Septal Cartilage–Derived Progenitor Cells during Prolonged Cultivation

Abstract: Objective To produce alternate cell sources for tissue regeneration, human nasal septal cartilage-derived progenitor cells (NSPs) were tested to identify whether these cells meet the criteria of cartilage progenitor cells. We also evaluated the effects of prolonged cultivation on the characteristics of NSPs. Study Design In vitro study. Setting Academic research laboratory. Methods NSPs were isolated from discarded human nasal septal cartilage. NSPs were cultured for 10 passages. The expression of septal proge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Low-passage (up to P3) human nasal septal chondrocytes have shown the capability to produce neocartilage containing GAG and type II collagen [89,90,99,[105][106][107]. It has also been suggested that the superficial zone of septal cartilage contains a promising population of nasoseptal progenitor cells (NSPs) [108]. These cells are migratory and express surface markers, such as CD29, CD105, CD106, CD90, and CCD44, suggesting a state of differentiation between mesenchymal stem cells (MSCs) and chondrocytes [109].…”
Section: : Nasal Cartilage Tissue-engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-passage (up to P3) human nasal septal chondrocytes have shown the capability to produce neocartilage containing GAG and type II collagen [89,90,99,[105][106][107]. It has also been suggested that the superficial zone of septal cartilage contains a promising population of nasoseptal progenitor cells (NSPs) [108]. These cells are migratory and express surface markers, such as CD29, CD105, CD106, CD90, and CCD44, suggesting a state of differentiation between mesenchymal stem cells (MSCs) and chondrocytes [109].…”
Section: : Nasal Cartilage Tissue-engineeringmentioning
confidence: 99%
“…NSPs have been shown to differentiate to chondrogenic and osteogenic, but not adipogenic lineages [88] and show a greater proliferation potential than bone marrow-and adipose-derived MSCs [110]. The surface markers and differentiation potential of NSPs have been reported to remain unchanged after 10 passages [108]. The use of both septal chondrocytes and NSPs are limited greatly by donor site morbidity and tissue availability.…”
Section: : Nasal Cartilage Tissue-engineeringmentioning
confidence: 99%
“…Heatmap representing the proportion of publications by year that utilized specific translational research methodologies from construct characterization to human trial to investigate nasal tissue engineering 8‐24,98‐106 …”
Section: Discussionmentioning
confidence: 99%
“…Utilization of human chondrocytes for cartilage regeneration has been a focus within nasal TE. Nasal septal chondrocytes, in particular, have been shown to have favorable proliferative capacity and chondrogenic potential compared to other chondrocyte sources in in vitro studies 23,24 . This tissue is easily acquired, either as remnants from septal surgery or as a biopsy of the septum with minimal donor site morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…All the studies using nasal septal chondrocytes (NSCs) were conducted after written approval (HC13TISI0038) obtained from the Institutional Review Board of the Catholic Medical Center Clinical Research Coordinating Center. Human nasal septum tissue was harvested from ve patients who were undergoing septoplasty [21]. Those tissues were cut into 1 mm 3 pieces and they were enzymatically digested using 0.2% protease solution (Gibco) for 60 min, followed by incubation in 0.3% collagenase (Sigma-Aldrich) for 12hr at 37 °C.…”
Section: Nasal Septal Chondrocytes (Nscs) Isolationmentioning
confidence: 99%